An overview of human infections / Review Article - Suhad Y Abed; Shahla Hussien Huno; Enaam Hameed Batah; Abdalkader Saeed Latif (Peerian Journals Publishing, 2024)
Microbes of all kinds spread around us, whether they are viruses or bacteria, and perhaps some may wonder about the difference between a virus and bacteria, especially after the spread of the Corona virus pandemic, which caused some concepts to be confused and to treat the virus as if it were a bacterial infection, which called on doctors to try to correct misconceptions, explaining the difference between viruses and bacteria, methods of treating both viruses and bacteria are transmitted to humans
Keywords: Human Infections; Pathogenic; Virus and Bacteria